Determination of the Development Strategy for the Labuan Bajo Waterfront Based on Visitor Satisfaction - Roseven Rudiyanto; Septian Hutagalung; Laurensius Sandrio; Marius Yosef Seran (EDUTOURISM Journal Of Tourism Research, 2023)
The existence of the Labuan Bajo Waterfront is relatively new. However, the Labuan Bajo Waterfront itself has become a tourist attraction in Labuan Bajo. Therefore, a study is needed to determine tourist satisfaction with the Labuan Bajo Waterfront and design a strategy to increase this satisfaction, especially in the attractions, accessibility, and amenities components. The sampling technique used in this study was random sampling with a questionnaire as a data collection technique. This study used the Likert scale to analyze the level of tourist satisfaction and determine the design strategy using the importance-performance analysis (IPA) method. In this study, the data collected came from 194 respondents. The results showed that tourist satisfaction with the Labuan Bajo Waterfront was very satisfied. In addition, the results of the IPA method show that the Concentrate Here Quadrant is related to cleanliness and safety; items in the Keep The Good Work Quadrant are the condition of the pier or walk board, lighthouse, road leading, footpaths in the Water Front area, ease of visiting the Water Front area, seating/rest facilities, and vehicle parking areas; items in the Low Priority Quadrant are road signs leading to the Water Front Area, trash bins, lighting, information boards, and eating and drinking facilities. The Possible Overkill Quadrant is related to tourism/entertainment activities in the Waterfront Area. Thus, even though the satisfaction level of Waterfront visitors is very satisfied, a destination development strategy is needed to improve quality related to cleanliness and safety.